(untitled) (Research, Society and Development, 2021)
Changes in the immune system caused by HIV characterize the Acquired Immune Deficiency Syndrome (AIDS), which makes the host’s organism susceptible to aggression from exogenous agents, providing opportunistic infections by oncogenic strains. There are few studies that address the issue of cancers associated with HIV, which makes this review important to address the epidemiological factors of the relationship between cancer and HIV. The study is an integrative review of publications from 2009 to 2019, available in Portuguese and English. The search was carried out in Lilacs, PubMed and SciELO databases. To analyze the methodological quality, the adapted Critical Appraisal Skill Program (CASP) and the adapted Agency for Healthcare and Research and Quality (AHRQ) were used. Non-Hodgkin’s lymphoma (NHL), Kaposi’s sarcoma (KS) and invasive cervical carcinoma have the highest prevalence rates as the most frequent neoplasms in HIV/AIDS prevalent, considered to define AIDS. In addition, male gender and white race were the most related to the development of neoplasms in people living with HIV/AIDS.